The Effect of Profitability, Leverage, Managerial Ownership, Dividend Policy on Income Smoothing and Audit Quality Moderation - Mualifah, Ninik Indah; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of profitability, leverage, managerial ownership, and dividend policy on income smoothing through moderation of audit quality. The sample in this study is financial and banking sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. This study uses a purposive sampling technique, data was obtained from 11 companies so that the sample used was 55 research data. In this study, logistic regression analysis was used using SPSS 27 as a calculation tool. Based on the test results, the variables of profitability, managerial ownership, and dividend policy have no effect on income smoothing, while leverage has a significant positive effect on income smoothing. Meanwhile, the audit quality moderation variable is not able to moderate the influence of leverage and managerial ownership on income smoothing. However, audit quality is able to strengthen the influence of profitability, and dividend policy on income smoothing.